NEXT – Graphical Editor for Authoring NCL Documents Supporting Composite Templates - Silva, Júlia Varanda da; Muchaluat-Saade, Débora Christina (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2012)
Interactive multimedia application development can be facilitated and more attractive to non-expert authors through the use of graphical editors. In a graphical environment that permits creation and edition of multimedia documents and offers different views of the document as a whole, it is possible to develop applications with less difficulty. In addition, if the editor provides templates, the development can be easier as, in that case, the author can use a pre-configured document and fulfill it with its own media content. This paper presents NEXT - NCL Editor supporting XTemplate, a graphical editor that allows development of NCL documents using hypermedia composite templates, which represent generic structures of NCL context nodes. Composite templates can be created with the XTemplate 3.0 language. Besides supporting templates, NEXT is based on a kernel and a set of plugins, which allow its extensibility and adaptability to different author skills.